2009
DOI: 10.1051/forest/2009037
|View full text |Cite
|
Sign up to set email alerts
|

Generation de marqueurs de séquences exprimées et développement de marqueurs microsatellites pour Castanopsis sieboldii var. sieboldii (Fagaceae)

Abstract: Abstract• Castanopsis sieboldii var. sieboldii is an evergreen broadleaved canopy tree that grows on Honshu, Shikoku and Kyushu Islands in Japan. A closely-related, hybridizing, congener species, C. cuspidata var. cuspidata, has different leaf epidermis structure and different seed nuts morphology compared to C. sieboldii var. sieboldii. Furthermore, the habitats in which the two species grow often indicate different water requirements.• Analysis of genetic diversity, using transcribed sequences, will provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…The frequencies of SSR types and motifs that we found in C. mollissima ESTs are in general agreement with those reported for other species in the Fagaceae Ueno et al 2009;Inoue et al 2009;Cheng and Huang 2009;Durand et al 2010). Based on our SSR search criteria, 18.1 % of the 48,335 C. mollissima CCall_Unige-ne_V2 ESTs contained at least one SSR.…”
Section: Marker Identification and Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…The frequencies of SSR types and motifs that we found in C. mollissima ESTs are in general agreement with those reported for other species in the Fagaceae Ueno et al 2009;Inoue et al 2009;Cheng and Huang 2009;Durand et al 2010). Based on our SSR search criteria, 18.1 % of the 48,335 C. mollissima CCall_Unige-ne_V2 ESTs contained at least one SSR.…”
Section: Marker Identification and Characterizationsupporting
confidence: 90%
“…Based on our SSR search criteria, 18.1 % of the 48,335 C. mollissima CCall_Unige-ne_V2 ESTs contained at least one SSR. A search for SSRs in Castanopsis sieboldii ESTs (Ueno et al 2009) found 13 % to contain at least one SSR. Similarly, 18.6 % of Quercus ESTs (Durand et al 2010) contained at least one SSR.…”
Section: Marker Identification and Characterizationmentioning
confidence: 99%
“…A total of 168 EST-SSR primer pairs, including 124 polymorphic EST-SSRs in Castanea mollissima (www.fagaceae.org), 16 in Castanopsis sieboldii (Ueno et al, 2009) and 28 in Quercus mongolica , were screened in a pilot experiment using 20 individuals of C. fargesii. Finally, 32 primer pairs (Table 2) with clear, polymorphic banding patterns were picked to genotype all individuals.…”
Section: Samples Dna Extraction and Est-ssr Genotypingmentioning
confidence: 99%
“…Three loci (CC20303, CcC02075 and CcC02464) was identified as possibly being under balancing selection. The first two loci were linked to uncharacterized protein, while CcC02464 assigned to a 5 0 -nucleotidase SurE-like survival protein in Arabidopsis (Ueno et al, 2009).…”
Section: Figurementioning
confidence: 99%
“…crispula (Ueno et al 2008), Castanopsis sieboldii (Ueno et al 2009a), and Fagus crenata (Ueno et al 2009b) to develop genic microsatellite (SSR) markers. Because SSRs are frequent within ESTs, they are a good source of genetic markers with functional annotation, though SSR frequency varies depending on the program and criteria used for SSR detection (12.8 % for Q. mongolica var.…”
Section: Large Scale Transcriptomic Investigationsmentioning
confidence: 99%